Pengaruh Ukuran Perusahaan, Konsentrasi Kepemilikan, Reputasi Auditor dan Risk Management Committee terhadap Pengungkapan Enterprise Risk Management - Fayola, Desak Nyoman Wiona Budi; Nurbaiti, Annisa (Universitas Pendidikan Ganesha, 2020)
This study aims to examine the effect of firm size, ownership concentration, auditorâ€™s reputation and risk management committee on the disclosure of enterprise risk management in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018. The sample selection technique used is puposive sampling and acquired 41 banking companies in the 2015-2018 so that the total sample used in this study are 164 samples. The data analysis method used is multiple linear regression analysis using Eviews version 10. The results found that simultaneous firm size, ownership concentration, auditorâ€™s reputation, and risk management committee influence the disclosure of enterprise risk management. Based on partial testing, firm size has a positive effect and ownership concentration negatively influences the disclosure of enterprise risk management.Â